2017
DOI: 10.1007/s10661-017-6279-6
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological risk infection assessment using QMRA in agriculture systems in Côte d’Ivoire, West Africa

Abstract: Poor wastewater management that results from a lack of appropriate sanitation infrastructure contributes to increasing health risks in urban areas in Côte d’Ivoire. We assessed the health risks associated with the use of wastewater for watering salad destined for human consumption, to help local authorities in developing appropriate risk mitigation measures for Yamoussoukro, the political capital of Côte d’Ivoire. We applied a stochastic approach based on quantitative microbiological risk assessment (QMRA), fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 27 publications
2
18
0
3
Order By: Relevance
“…Other authors assessed potential contamination of urban soil and UA produce by heavy metals. Most of them agreed that accidental ingestion of UA soil [106, 115, 116, 119] or consumption of vegetables or other produce grown in contaminated UA soil [15, 16, 106, 107, 112–114, 118] may represent a risk for the health of different population groups (e.g. children and/or adults).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors assessed potential contamination of urban soil and UA produce by heavy metals. Most of them agreed that accidental ingestion of UA soil [106, 115, 116, 119] or consumption of vegetables or other produce grown in contaminated UA soil [15, 16, 106, 107, 112–114, 118] may represent a risk for the health of different population groups (e.g. children and/or adults).…”
Section: Resultsmentioning
confidence: 99%
“…Adverse impacts of UA have also been reported by the public health community and urban planners. Several studies showed UA practices can influence food safety because of the risks associated to urban soil or water contamination [15, 16]. Other studies have pointed out the facts that urban gardening can be a place where certain participants feel excluded or it can also be a place where existing race and social class-based disparities are replicated [17].…”
Section: Introductionmentioning
confidence: 99%
“…Sometimes, the vendors sprinkle water to the vegetables to give them a fresh and attractive look. Such incorrect practices lead to the occurrence of pathogens in fresh produce and the emergence of more cases of diseases associated with them, suggesting the need for tighter vendors’ supervision and their retraining about good health and sanitation practices [ 26 , 34 ]. The comparison of the gender issue with product sanitization showed that women are the ones who best adhere to the attitudes of good practices ( p = 0.008, Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…This analysis assumed that a single cell of E. coli O157:H7 will cause an infection and defines the relationship between the doses of E. coli O157:H7 and the corresponding negative health effects on the exposed population [23]. The ingestion dose of E. coli O157:H7 was therefore calculated using the following equation [24];…”
Section: Hazard Characterizationmentioning
confidence: 99%
“…where P inf denotes the probability of infection that will occur in an individual exposed to a particular dose (D) of E. coli O157:H7, D denotes the ingestion dose of E. coli O157:H7, α and β denote the shape parameters and in this case, α is 0.0571 and β is 2.2183 [24].…”
Section: Hazard Characterizationmentioning
confidence: 99%